PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XII DI SMK NEGERI 4 MALANG - Devi Pujiyanti; Ach. Faisol; Muhammad Sulistiono (VICRATINA, 2021)
The development of information technology in the world of education is currently growing rapidly. The impact cannot be avoided anymore, so the role of the government is needed to make adjustments to improve the quality of education. Information and Communication Technology is expected to provide great opportunities for improving the quality of learning effectively. Based on preliminary observations, during the Covid -19 pandemic, teachers tried to apply the Project Based Learning learning model in SMK Negeri 4 Malang. This study aims to motivate student learning and improve student learning outcomes in Islamic Religious Education learning using online learning methods during the Covid -19 Pandemic. This research is a type of classroom action research, with a qualitative approach to the Kemmis & McTaggart Research Design Model, which aims to obtain a representative learning cycle according to predetermined criteria and the number of cycles obtained is 2 cycles. The results of this study indicate that the completeness of student learning outcomes while using the Project Based Learning learning model during the Covid-19 pandemic, in the heir chapter shows significant